JClic y nociones lógico-matemáticas en niños de preparatoria, de la Escuela de Educación Básica Julio María Matovelle, de la ciudad de Loja, en el periodo académico 2022-2023 - Llivigañay Guaillas, Micaela Katherine (2024)
The research denominated JClic and logical-mathematical notions in high school children, from the Julio María Matovelle Basic Education School, in the city of Loja, in the 2022-2023 academic period, sought to determine how the JClic program strengthens logical-mathematical notions in 5-year-old children, the methodology was developed under a mixed approach and a descriptive design, using the inductive deductive and analytical-synthetic methods that allowed to investigate and externalize precise and relevant information in order to support the curricular integration work, direct observation and evaluation instruments such as a checklist were applied, the EVAMAT-0 Test was also used which was applied to 20 children, who constituted the study sample. Regarding the results of the pretest, it could be seen that within the geometry dimension, 9 children correspond to 45%, in the quantity and counting dimension, 15 children correspond to 75% and in problem solving, 19 children correspond to 95%, in order to denote in this way the main difficulties existing at the logical-mathematical level. In order to solve the problem, an activity guide was developed and designed and with the application of the posttest it was possible to considerably optimize the level of logical-mathematical notions, 90% of the children managed to reach the high zone in their mathematical capacities, reaching the conclusion that the JClic educational platform, which was progressively used in the intervention, allowed to improve the logical-mathematical notions, favoring in children the concentration, discrimination, analysis and comprehension for the resolution of problems of mathematical competencies. Keywords: mathematical field, competencies, innovation, meaningful learning, educational software.